2019
DOI: 10.1111/poms.13003
|View full text |Cite
|
Sign up to set email alerts
|

Information Provision and Pricing in the Presence of Consumer Search Costs

Abstract: Should a seller make information about its products readily accessible to customers, so that customers do not have to incur any substantive cost—in terms of time and effort—to learn about those products? To help answer this question, we consider a monopolist selling two substitute products to a population of customers, who have differing tastes about the products. Each customer a priori has uncertainty about whether or not he will like each of the products. The seller may choose to make product information eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 39 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Liu et al. (2019) find that in the presence of a search cost, the seller may choose to make its product information easily accessible, thereby allowing customers to resolve their product valuation uncertainties for free. A recent review of both quality disclosure and information provision literature is available in Gu and Chen (2019).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. (2019) find that in the presence of a search cost, the seller may choose to make its product information easily accessible, thereby allowing customers to resolve their product valuation uncertainties for free. A recent review of both quality disclosure and information provision literature is available in Gu and Chen (2019).…”
Section: Related Literaturementioning
confidence: 99%
“…For example, Wang et al (2018) examine the interaction of information provision and pricing decisions for competitive firms, and characterize the equilibrium prices. Liu et al (2019) find that in the presence of a search cost, the seller may choose to make its product information easily accessible, thereby allowing customers to resolve their product valuation uncertainties for free. A recent review of both quality disclosure and information provision literature is available in Gu and Chen (2019).…”
Section: Related Literaturementioning
confidence: 99%
“…The recent rise of online search/ reviews offers easy access to customers to learn about the quality of products. Liu et al (2019) allow customers to conduct research to resolve valuation uncertainties by incurring a search cost. The authors show that information disclosure depends on customers' uncertainties in their valuations of the product and the magnitude of customers' search costs.…”
Section: Product Information Disclosurementioning
confidence: 99%
“…Our work enriches our understanding of information disclosure when customers have heterogeneous biased perceptions about product quality. A large body of literature has identified factors that affect sellers' disclosure decision (e.g., Liu et al 2019, Zhu et al 2021. We extend the literature by looking at multiple decisions on information disclosure over time, since we are considering deteriorating fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have shown that manufacturers as participants in the supply chain can also share information in some cases where the manufacturer possesses better demand information than the downstream retailer ( Jiang et al, 2016 ; Zhou et al, 2017 ; He et al, 2018 ). In addition, information sharing may occur between retailers and consumers ( Liu Y. et al, 2019 ). Absolutely, some studies look at information sharing within an enterprise where the sales department is responsible for forecasting demand and the operations department is responsible for ordering ( Scheele et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%